2005
DOI: 10.1302/0301-620x.87b1.15146
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of dislocation of the hip in children with cerebral palsy

Abstract: In 1994, a register for cerebral palsy and a health-care programme were started in southern Sweden with the aim of preventing dislocation of the hip in children with cerebral palsy. It involved all children with cerebral palsy born in 1992 or later. None of the 206 affected children born between 1992 and 1997 has developed a dislocation following the introduction of the prevention programme. Another 48 children moved into the area and none developed any further dislocation. Of the 251 children with cerebral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(85 citation statements)
references
References 27 publications
2
70
0
13
Order By: Relevance
“…This is supported by a study highlighting pain from spasticity and muscle spasms in children (19), and further by a study demonstrating that hip dislocation in CP sufferers can result in serious problems such as pain, contractions, discomfort when seated, misaligned pelvis and scoliosis (22). The results of our study also show that parents experience the children's pain to diminish after hip and scoliosis operations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This is supported by a study highlighting pain from spasticity and muscle spasms in children (19), and further by a study demonstrating that hip dislocation in CP sufferers can result in serious problems such as pain, contractions, discomfort when seated, misaligned pelvis and scoliosis (22). The results of our study also show that parents experience the children's pain to diminish after hip and scoliosis operations.…”
Section: Discussionsupporting
confidence: 86%
“…The results of our study also show that parents experience the children's pain to diminish after hip and scoliosis operations. Since 1994, the Cerebral Palsy standardized follow-up program (CPUP) has been in existence for children with CP in Sweden (22,23). Results show a decrease in hip luxation and other complications such as contractions, skeletal deformation and scoliosis (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevention programme involving 206 children with cerebral palsy at 5 years of age reported that none had developed hip dislocation 13. However, many of these children were walking, and many had had surgery (48 soft tissue or bone surgical interventions, 9 selective dorsal rhizotomies, and the insertion of 3 intrathecal baclofen delivery systems).…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Many studies on both soft tissue and bone surgery have a short follow-up, and studies cannot be compared because they lack valid functional outcomes, pain is not measured systematically before and after surgery, or they use different combinations of procedures 8 13…”
Section: Treatment Approachesmentioning
confidence: 99%